Brand Authenticity Effects On Brand Image : Brand Study Of Converse Sneakers For Gen Z - Helma, Alifia Saadatul; Andika, Muhammad Farid; Apriyana, Nurliya (SEAN Institute, 2024)
The swift transformation of the fashion industry, driven by the distinct preferences of Generation Z, has turned sneakers from mere functional footwear into emblems of social status and personal identity. Among the leading brands in this sector is Converse, which consistently secures its status as a top brand through a blend of quality, exclusivity, and authenticity. However, the influence of brand authenticity—comprising originality, perceived value, and continuity—on shaping brand image remains insufficiently explored. This study examines how these aspects of brand authenticity affect the brand image of Converse sneakers among Generation Z in Jabodetabek. Utilizing purposive sampling, 100 respondents aged 18 to 27 participated in this research via an online questionnaire. The analysis conducted with SEM-PLS reveals that originality does not have a significant impact on brand image, while perceived value and continuity positively and significantly influence it. These findings underscore the importance of perceived quality and a consistent brand identity in establishing a robust brand image. It is recommended that Converse focus on delivering exceptional value and maintaining its authenticity to foster loyalty within the Gen Z demographic.